Propeller jet induced erosion around pile supported berth structures - Tan, Remziye İlayda (My University, 2019)
This thesis presents an improvement for the assessment of scour effects owing to propeller jet velocities with a direct application to prototype modeling by conducting a non-dimensional analysis. This study provides insights on the scouring problems owing to a propeller jet. In order to overcome the limitations found in the literature, expanded densimetric Froude numbers (1.95 ≤ Frd ≤ 15.01) were used. Experimental tests were developed for this purpose and formulae recommendations are provided to enhance the estimation of different relevant parameters of the scour process. In addition, the experimental conditions were extended, by ranging sand beds from finer to coarser that were d50 = 0.52 mm, 1.28 mm, 4.00 mm and 8.30 mm, and the Frd were compared with the ones stated in the previous studies. Hence, this study has proposed new formulae to predict the scouring owing to propeller jet flows. Scaling of the experimental model have been explained and the experimental conditions have been given. An acoustic Doppler velocimeter (ADV) was used to obtain the propeller velocity. In order to calculate the magnitude of efflux velocity a new equation is proposed, considering the propeller geometry and characteristics. Thus, it has been aimed to improve the level of knowledge that already exists in the literature. In addition, the scour induced by a propeller jet around a single pile was examined experimentally. The initiation of scour formation was found to be related to the densimetric Froude number (Frd), propeller diameter (Dp), and the gap of the propeller (G), which is defined as the vertical distance between the centerline of the propeller and the undisturbed sand bed. Three types of scour profiles were defined that can be classified according to a) the scour depth at the upstream toe of the pile (So), and b) the scour at the downstream section of the pile (Sd). Scour profiles were found to be highly dependent on the densimetric Froude number (Frd) and pile diameter (do). Scour profiles and scour depths at the toe of the pile (So) were investigated at different distances between pile locations and propeller face (X), pile diameter, sediment bed material size, propeller diameter, speed, and gap. New empirical equations were proposed for the estimation of the scour depth at the toe of the pile. The locations of the pile (X) were also investigated to assess whether the predominant scouring mechanism was the propeller jet or the pile mechanism. Furthermore, scour formations around the two - pile tandem arrangements with different pile diameters (do= 4 cm and 9 cm) and sediment beds (d50 = 0.52 mm, 1.28 mm), and the application of rock protection around a pile case at at a constant propeller diameter, speed and gap were investigated.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2019
Keywords: Scour; Propeller jet; Berth structures; Propeller wash; Water jet